Persepsi Konsumen Terhadap Harga dan Pelayanan di Point Coffee Indomaret Pondok Chandra - Mirza Nuria Husna; Akhmad Yunan Atho’illah (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to describe consumer perceptions of price and service quality at Point Coffee Indomaret Pondok Chandra. A descriptive qualitative approach was applied, with data collected through interviews and observations of customers who had purchased products at the location. The results show that consumers perceive the service as satisfying due to fast transactions, responsive employees, and minimal waiting time. Meanwhile, the price is viewed as relatively mid-to-high, but still acceptable because the service benefits are considered proportional to the cost. Thus, service quality becomes a more dominant factor than nominal price in shaping consumer acceptance.